Mosquitoland - Arnold, David, 1981- (New York : Viking, 2015)
"When she learns that her mother is sick in Ohio, Mim confronts her demons on a thousand-mile odyssey from Mississippi that redefines her notions of love, loyalty, and what it means to be sane"--
English language and literature.
Keywords: Voyages and travels -- Fiction; Runaways -- Fiction; Mothers and daughters -- Fiction; Mental illness -- Fiction; Stepfamilies -- Fiction